"Self-development matters" - Perception of Sakhis (CHWs) assessing self-development outcomes of their participation in the HBNC Program - Anagha Anand Mahajani; Abhijit Shrinivas Prabhughate; Pearl Tiwari; Shubhangi Sohoni; Ajay Gajanan Phatak; Vallaree Anant Morgaonkar; Somashekhar Marutirao Nimbalkar (BMC, 2018)
Abstract Background Community Health Workers (CHWs) play an instrumental role in promoting socio-behavioural change at the community level, which results in changed indicators of community health. While outcomes are mostly reviewed for achieving program objectives, it is pertinent to understand the process of program implementation mainly from the perception of participating CHWs. Methods A qualitative study to understand the perception of Sakhi's (CHWs) regarding the outcomes of their participation in Home-Based Neonatal Care (HBNC) Program implemented by a non-governmental organization (NGO). Data consisted of 3 FGDs and 20 in-depth unstructured interviews with participating Sakhis. Results Sakhis perceived their ability to take decisions at critical phases of the program as an important factor influencing their performance. The opportunity to participate as a Sakhi in the health programme initiated a process of change at the personal level. The changes perceived by Sakhis were enhancement in knowledge, skills and capabilities of Sakhis. The combination of improved skills, knowledge and attitude had culminated in the process of experiencing self-empowerment for the participating Sakhis. Their ability to positively influence the individuals and community with their initiatives to improve women and child health and save lives in critical situations facilitated development of a new identity and improved societal status in their communities. Changed power-relations at the family and community level promoted the involvement of Sakhis in the broader development agenda. Sakhis' ability to strategize goals, evaluate their own abilities, their willingness to upgrade knowledge and take others along in bringing social change, was an evident movement towards self-development. Conclusion An opportunity for local women to participate in development programs creates potential for self-development as a cascading effect in addition to the accomplishment of planned program objective.